Hispanics and the Future of America - Tienda, Marta; Mitchell, Faith; National Research Council (U.S.). Panel on Hispanics in the United States; National Research Council (U.S.). Committee on Population (National Academies Press, 2006)
Hispanics and the Future of America presents details of the complex story of a population that varies in many dimensions, including national origin, immigration status, and generation. The papers in this volume draw on a wide variety of data sources to describe the contours of this population, from the perspectives of history, demography, geography, education, family, employment, economic well-being, health, and political engagement. They provide a rich source of information for researchers, policy makers, and others who want to better understand the fast-growing and diverse population that we call "Hispanic." The current period is a critical one for getting a better understanding of how Hispanics are being shaped by the U.S. experience. This will, in turn, affect the United States and the contours of the Hispanic future remain uncertain. The uncertainties include such issues as whether Hispanics, especially immigrants, improve their educational attainment and fluency in English and thereby improve their economic position; whether growing numbers of foreign-born Hispanics become citizens and achieve empowerment at the ballot box and through elected office; whether impending health problems are successfully averted; and whether Hispanics' geographic dispersal accelerates their spatial and social integration. The papers in this volume provide invaluable information to explore these issues.